2015
DOI: 10.1109/tmi.2015.2411571
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Order Motion-Compensation for In Vivo Cardiac Diffusion Tensor Imaging in Rats

Abstract: Motion of the heart has complicated in vivo applications of cardiac diffusion MRI and diffusion tensor imaging (DTI), especially in small animals such as rats where ultra-high-performance gradient sets are currently not available. Even with velocity compensation via, for example, bipolar encoding pulses, the variable shot-to-shot residual motion-induced spin phase can still give rise to pronounced artifacts. This study presents diffusion-encoding schemes that are designed to compensate for higher-order motion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
84
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 53 publications
2
84
0
Order By: Relevance
“…1 While historically the DTI literature has focussed on the brain, 2 recent developments in diffusion tensor cardiovascular magnetic resonance (DT-CMR) have overcome the difficulties associated with measuring diffusion in the dynamic environment of the heart. [3][4][5][6][7][8] This has facilitated in-vivo assessment of microstructural abnormalities in a number of patient cohorts. [9][10][11][12] The nature of a beating heart means that traditional Stejskal-Tanner-type diffusion-weighted spin echo techniques cannot be used.…”
Section: Introductionmentioning
confidence: 99%
“…1 While historically the DTI literature has focussed on the brain, 2 recent developments in diffusion tensor cardiovascular magnetic resonance (DT-CMR) have overcome the difficulties associated with measuring diffusion in the dynamic environment of the heart. [3][4][5][6][7][8] This has facilitated in-vivo assessment of microstructural abnormalities in a number of patient cohorts. [9][10][11][12] The nature of a beating heart means that traditional Stejskal-Tanner-type diffusion-weighted spin echo techniques cannot be used.…”
Section: Introductionmentioning
confidence: 99%
“…With recent improvements in gradient hardware becoming widely available on clinical MR systems and dedicated diffusion gradient designs, diffusion weighted single-shot spinecho (SE) sequences have become feasible for in vivo cardiac DTI. Several studies have shown that signal attenuation due to myocardial motion can be addressed successfully by incorporating motion compensated diffusion gradient waveforms (17,19,(35)(36)(37)(38)(40)(41)(42)(43). Promising results of the in vivo human (38) and rat (42) heart using second and third order motion compensated DTI have been presented recently.…”
Section: Introductionmentioning
confidence: 99%
“…DTI has emerged as a preferred technique for noninvasive quantifications of myocardial structures. Although the feasibility of in vivo cardiac DTI has long been demonstrated , recent advances in both gradient hardware and imaging technologies have made in vivo cardiac DTI more widely used . The principal direction of diffusion anisotropy (i.e.…”
Section: Introductionmentioning
confidence: 99%